THE INFLUENCE OF STORE ATTEMPT AND SALES PROMOTION ON CONSUMER PURCHASE DECISIONS OF RAMAYANA DEPARTMENT STORE IN SERANG CITY - Edy Suranta Karina Sembiring; Udin Bahrudin (Amal Insani Foundation, 2021)
The purpose of this study was to determine the effect of store atmosphere on consumer purchasing decisions, to determine the effect of sales promotion on consumer purchasing decisions and to determine the effect of store atmosphere and sales promotion on consumer purchasing decisions of Ramayana Department Store in Serang City. This study uses quantitative research methods, quantitative research methods can be interpreted as research methods based on the philosophy of positivism, used to examine certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/ statistics with the aim of testing the established hypothesis. The population in this study are consumers or visitors of Ramayana Serang who have made purchases at Ramayana Serang City. The results of testing hypothesis 1 show that the atmosphere of the store has a significant effect on consumer purchasing decisions at the Ramayana Department Store in Serang City, in this case if the atmosphere of the store increases, the decision will increase. The results of testing hypothesis 2 show that sales promotions have a significant effect on consumer purchasing decisions for Ramayana Department Stores in Serang City. In this case, if sales promotions increase, the decisions will increase. The results of the submission of hypothesis 3 show that the store atmosphere and sales promotions have a significant effect on consumer purchasing decisions at the Ramayana Department Store in Serang City, this is if the store atmosphere and sales promotions increase, consumer purchasing decisions will increase. Keywords: Store Atmosphere, Sales Promotion and Consumer Purchase Decisions